If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 96 + -7x = 20x + 24 Reorder the terms: 96 + -7x = 24 + 20x Solving 96 + -7x = 24 + 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. 96 + -7x + -20x = 24 + 20x + -20x Combine like terms: -7x + -20x = -27x 96 + -27x = 24 + 20x + -20x Combine like terms: 20x + -20x = 0 96 + -27x = 24 + 0 96 + -27x = 24 Add '-96' to each side of the equation. 96 + -96 + -27x = 24 + -96 Combine like terms: 96 + -96 = 0 0 + -27x = 24 + -96 -27x = 24 + -96 Combine like terms: 24 + -96 = -72 -27x = -72 Divide each side by '-27'. x = 2.666666667 Simplifying x = 2.666666667
| 7(a+7)=86.1 | | 4x+2(3-x)=2x-5 | | 24.7=9c-5 | | 3e-3=12.6 | | 8p=34.4 | | 8(x-8)=-48 | | 4(a+2)=44 | | 5e-2=8 | | 5e-2=18 | | m+n=r | | 11-8x=-109 | | 11x-4=-5 | | y=-1/2x-2 | | 59=7x-11 | | 13+6x=61 | | 3*(4a-3)=-2a-2a+23 | | 8x-7=105 | | 3x(4a-3)=-2a-2a+23 | | x+2/2=7-x+1/3 | | 2x^3/2*-3^-3/2 | | 2(y-3)=20 | | 125*x^5-171*x^4+103*x^3+224*x^2-508*x+240=0 | | x+x+15+4x-22=1139 | | 2(x-7)=6x+10 | | 65-4x=14x+21 | | 10-3=(2x-1) | | 10-3=5(d-4) | | 10x+30=-5x | | 25^(-3/2) | | 4c+8=-88-8x | | Z=ax^2+3by | | 2*x^4-3*x^3+3*x^2-3*x+2=0 |